Exploration and prospect on the application of digital twin in rail transit electric traction systems - SONG Wensheng; ZHANG Sihui; YE Cunxin; ZHANG Zhiwei; ZOU Yuchao (机车电传动)
With the rapid development and technological maturity of China's rail transit electric traction system, its reliability assessment and intelligent monitoring technology have gradually attracted attention. Digital twin, as a virtual characterization technique for actual physical systems based on data and machine learning, can simulate the behavioral characteristics and monitor parameters of actual physical systems. Therefore, introducing digital twin technology into the rail transit electric traction system field can provide development ideas and technical means for the digital and intelligent monitoring and operation & maintenance of these systems. This paper first provides an overview of the current application of digital twin technology in electric traction systems, and then lists the key technologies required in the construction process of digital twin in electric traction systems and the development of these technologies. In the electric traction system field, digital twin and related technologies are still in the theoretical research stage, with only exploratory research on some subsystems available, and the complete system modeling and intelligent monitoring system has not yet formed. Finally, this paper looks forward to the engineering implementation prospects of digital twin technology in the electric traction system field, and discusses the internal technical problems and external objective challenges it may face when applied in engineering, for providing a reference for the subsequent technical research and practice.